Kolaborasi Karang Taruna dan Pemuda Hadroh dalam Menciptakan Suasana Idul Adha yang Islami dan Bermakna di Desa Rejosari, Lampung Utara - Putri Pebrinawati; Rino Pambudi; Martoyo Martoyo (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Eid al-Adha is an important moment in the Islamic religion which is full of values ​​of sacrifice, solidarity and social concern. However, in some cases, the essence of this celebration is often forgotten and becomes mere routine. This article discusses efforts to revive the meaning of Eid al-Adha in Rejosari Kaliopak Village, Kotabumi District, North Lampung Regency, through collaboration between Karang Taruna and the Hadroh youth group. This collaboration aims to create a celebratory atmosphere full of Islamic values, strengthen ties, and increase people's understanding of the meaning of Eid al-Adha. Activities carried out include religious recitations, slaughtering and distribution of sacrificial animals, hadroh art performances, as well as social service in the form of distributing basic necessities. The result of this collaboration is the creation of a more meaningful Eid al-Adha celebration, increasing community participation, and strengthening social solidarity. Apart from that, this activity also helps develop youth potential in the fields of religion and arts and culture, as well as forming a more responsible and disciplined youth character.